Age constraints on felsic intrusions, metamorphism and gold mineralisation in the Palaeoproterozoic Rio Itapicuru greenstone belt, NE Bahia State, Brazil - Mello, E.; Xavier, R.; McNaughton, Neal; Hagemann, S.; Fletcher, Ian; Snee, L. (Springer, 2006)
U-Pb sensitive high resolution ion microprobe mass spectrometer (SHRIMP) ages of zircon, monazite andxenotime crystals from felsic intrusive rocks from the Rio Itapicuru greenstone belt show two development stages between 2,152 and 2,130 Ma, and between 2,130 and 2,080 Ma. The older intrusions yielded ages of 2,1526 Main monazite crystals and 2,1559 Ma in zircon crystals derived from the Trilhado granodiorite, and ages of 2,1307 Ma and 2,1288 Ma in zircon crystals derived from the Teofilndia tonalite. The emplacement age of the syntectonic Ambrsio dome as indicated by a 2,0802-Maxenotime age for a granite dyke probably marks the end of the felsic magmatism. This age shows good agreement withthe Ar-Ar plateau age of 2,0805 Ma obtained in hornblendes from an amphibolite and with a U-PbSHRIMP age of 2,07610 Ma in detrital zircon crystals from a quartzite, interpreted as the age of the peak of the metamorphism. The predominance of inherited zircons in the syntectonic Ambrsio dome suggests that the basement of the supracrustal rocks was composed of Archaean continental crust with components of 2,93716, 3,11113 and 3,16213 Ma. Ar-Ar plateau ages of 2,0504 Ma and 2,0542 Ma on hydrothermal muscovite samples from the Fazenda Brasileiro gold deposit are interpreted as minimum ages for gold mineralisation and close to the true age of gold deposition. The Ar-Ar data indicate that the mineralisation must have occurred less than 30 million years after the peak of the metamorphism, or episodically between 2,080 Ma and 2,050 Ma, during uplift and exhumation of the orogen.